ISCOM-type matrix from beta-escin and glycyrrhizin saponins - V. Petkov; S. Tsibranska; I. Manoylov; L. Kechidzhieva; K. Ilieva; S. Bradyanova; N. Ralchev; N. Mihaylova; N. Denkov; A. Tchorbanov; S. Tcholakova (Heliyon)
Background and aims: Nanotechnology provides the opportunity for construction of modern transport devices such as nanoparticles for a variety of applications in the field of medicine. A novel experimental protocol for the formation of saponin-cholesterol-phospholipid nanoparticles of vesicular structure has been developed and applied to prepare stable nanoparticles using escin or glycyrrhizin as saponins. Methods: The methods for nanoparticle construction include a sonication at 90 °C of the initial mixture of components, followed by an additional sonication on the next day for incorporation of an additional amount of cholesterol, thus forming stable unilamellar vesicles. Tests and assays for cell viability, erythrocyte hemolysis, flow cytometry, and fluorescent microscopy analyses have been performed. Results: By selecting appropriate component ratios, stable and safe particles were formulated with respect to the tested bio-cells. The prepared nanoparticles have mean diameter between 70 and 130 nm, depending on their composition. The versatility of these nanoparticles allows for the encapsulation of various molecules, either within the vesicle interior for water-soluble components or within the vesicle walls for hydrophobic components. The saponin particles formed after cholesterol post-addition (E3-M2) are stable and 100 % of the cells remain viable even after 10-times dilution of the initial particle suspension. These particles are successful included into isolated mouse macrophages. Conclusions: Among the variety of generated nanoparticles, the E3-M2 particles demonstrated properties of safe and efficient devices for future vaccine design and antigen targeting to immune system.